2003
DOI: 10.1046/j.1526-4610.2003.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Locus of Control in Women With Migraine and Healthy Volunteers

Abstract: Our results suggest that migraineurs with aura differ from migraineurs without aura and healthy control subjects in terms of anxiety and depression. With regard to health-related locus of control, there was no correlation among mean number of migraine attacks per year, duration of disease, time of last migraine attack, and number of aura symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…We did not find differences in depression for headache types; therefore our results did not support previous research that observed between headache type differences for psychological symptoms [13, 15]. Also, our results did not support previous findings that a higher self-efficacy was associated with positive headache coping strategies [23].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find differences in depression for headache types; therefore our results did not support previous research that observed between headache type differences for psychological symptoms [13, 15]. Also, our results did not support previous findings that a higher self-efficacy was associated with positive headache coping strategies [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Other research has found differences in personality traits between migraineurs and healthy controls [14] and increased depression and anxiety among migraineurs with aura as opposed to migraineurs without aura [15]. The relationships among headache etiology, stress, coping styles and psychological factors have been addressed in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of MHLC (Forms A and B) refers to wide areas of functioning, health and medical conditions (see Wallston et al, 1978). This generality might also explain the lack of significant associations between the loci and specific measures of health status or health behaviors, such as compliance with fluid-intake restrictions among patients under haemodialysis (Pang, Ip, & Chang, 2001) or number of migraine attacks per year, duration of disease, time of last migraine attack and number of aura symptoms in patients with migraine (Lampi et al, 2003). When health behaviors are under examination, only small amounts of variance are accounted for by the general measure of health locus of control (see Bennett, Norman, Murphy, Moore, & Tudor-Smith, 1997;Steptoe & Wardle, 2001a, 2001b.…”
Section: General Condition-related and Outcome-specific Beliefs About Health Locus Of Controlmentioning
confidence: 99%
“…For example, psycho-educational interventions have increased the scores for E-LOC but not for I-LOC (33). In some studies, LOC has not been associated with disorder impact parameters (34,35) or with more adaptive coping with pain (12).…”
mentioning
confidence: 99%